2020
DOI: 10.1021/acs.bioconjchem.9b00867
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Conjugated Hydrogelators for Imaging and Therapeutic Applications

Abstract: In recent years, research on supramolecular hydrogels for biomedical applications developed rapidly by covalently conjugating their hydrogelators with functional moieties including therapeutic agents and imaging probes. Such conjugation can not only endow hydrogels with specific functions but also enhance the performance of the functional moieties. Therefore, these evolutionary conjugates may create a great leap for the application of supramolecular hydrogels in clinical scenarios, especially in a bioimaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…2 presents a schematic overview of biofunctionalized nanomaterial advantages in cancer theranostics. The biofunctionalization of nanomaterials can be done either through non-covalent interaction which includes physical adsorption, biomolecule entrapment, ionic interaction, or covalent interaction on nanomaterial surface [48] , [49] , [50] , [51] , [52] . The non-covalent functionalization results in maintaining the conjugated skeleton as well as the inherent electronic structure whereas covalent functionalization provides more stability and reproducibility for biofunctionalized nanomaterials [53] .…”
Section: Biofunctionalization Of Nanomaterials: Conjugation Strategiesmentioning
confidence: 99%
“…2 presents a schematic overview of biofunctionalized nanomaterial advantages in cancer theranostics. The biofunctionalization of nanomaterials can be done either through non-covalent interaction which includes physical adsorption, biomolecule entrapment, ionic interaction, or covalent interaction on nanomaterial surface [48] , [49] , [50] , [51] , [52] . The non-covalent functionalization results in maintaining the conjugated skeleton as well as the inherent electronic structure whereas covalent functionalization provides more stability and reproducibility for biofunctionalized nanomaterials [53] .…”
Section: Biofunctionalization Of Nanomaterials: Conjugation Strategiesmentioning
confidence: 99%
“…A powerful early-stage screening technique for cancer is tumor imaging [ 210 ]. Kim et al reported an injectable magnetic resonance imaging (MRI)-monitored long-term medicinal hydrogel (MLTH) for the recognition and localization of brain tumor tissues [ 211 ].…”
Section: Applications In Biochemistrymentioning
confidence: 99%
“…In view of the above situation, researchers proposed that nanomaterials based on micelles, liposomes or supramolecular hydrogels could provide a new alternative to improve the stability of therapeutic drugs and maintain the long-term retention in lesions [14][15][16]. Among them, supramolecular hydrogels formed by the self-assembling of the hydrogelators into three-dimensional fibrous networks to gel large amount of water, have higher biosafety, higher drug loading efficiency and are easier to be metabolized [17][18][19][20]. In recent years, they have been widely studied and applied in the biomedical field [21,22].…”
Section: Introductionmentioning
confidence: 99%